How does workplace ostracism affect employee innovation behavior: An analysis of chain mediating effect - Xing, Yimeng; Li, Yongzhou (Frontiers in Psychology, 2022)
This study seeks to examine the relationship between workplace ostracism and innovation behavior while considering the mediating role of knowledge hiding and organizational identification. The study also tests the moderating role of task interdependence in these relationships. The study collected data through structured questionnaires from 409 participants (i.e., employees) working in the small to medium-sized enterprise of big cities of China. The study adopted a structured equation modeling technique for data analysis. Significantly, the study results suggest that workplace ostracism is negatively associated with innovation behavior, both directly and indirectly via knowledge hiding and organizational identification. We also find that task interdependence weakens the positive relationship between workplace ostracism and knowledge hiding. Current study has tested the negative relationship between workplace ostracism and innovation behavior unlike most of the previous investigations that have focused on positive factors. Our study from a rational perspective to explore the influence mechanism between workplace ostracism and innovation behavior is addition to the previous research and the rich, in revelation managers motivate employees to implement knowledge sharing activities at the same time, pay attention to take measures to restrain negative knowledge such as knowledge hidden activities, to activate the creativity of organization staff of intellectual resources. This paper contributes to innovation behavior literature which is an important part of innovation management based on both conservation of resources theory and social network theory.